Living under a fluctuating climate and a drying Congo Basin - Sonwa, D.J.; Oumarou Farikou, M.; Martial, G.; Félix, F.L. (MDPI, 2020)
Humid conditions and equatorial forest in the Congo Basin have allowed for the maintenance of significant biodiversity and carbon stock. The ecological services and products of this forest are of high importance, particularly for smallholders living in forest landscapes and watersheds. Unfortunately, in addition to deforestation and forest degradation, climate change/variability are impacting this region, including both forests and populations. We developed three case studies based on field observations in Cameroon, the Central African Republic, and the Democratic Republic of Congo, as well as information from the literature. Our key findings are: (1) the forest-related water cycle of the Congo Basin is not stable, and is gradually changing; (2) climate change is impacting the water cycle of the basin; and, (3) the slow modification of the water cycle is affecting livelihoods in the Congo Basin. Developmental and environmental actions in the Congo Basin need to properly consider the slight modification of this water cycle in watersheds that affect products and services from the forest.